Slovene as a minority and foreign language in italian mainstream schools in the province of Trieste - Cavaion, Irina Moira (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2022)
This paper describes the history, presence, actions and perspective of Slovene language teaching and learning in Italian primary mainstream schools in the province of Trieste as an extraordinary opportunity - after 30 years of Slovenia’s independence and almost 25 years of open borders - to reflect on the role of Slovene as a minority and foreign language among the majority population of neighbouring Italy, on the interethnic relationships it fosters, and on its potential to become an element of identity awareness development within the process of identity formation for both the kin state Slovenia homeland and the Slovene community in Trieste.
Keywords: border regions; Jeziki v stiku; Jezikovna politika; language policy; neighbouring languages; obmejna območja; Pedagogika; Slovene as a foreign language; Slovene as a second language; Slovenščina; slovenščina kot drugi jezik; slovenščina kot tuj jezik; sosedski jeziki